Effect of nano silica on properties of concrete containing RCA - Shaikh, Faiz; Odoh, H.; Tahn, A. (ICE Publishing, 2014)
The effect of nano silica on mechanical and durability properties of concretes containing recycled coarse aggregates (RCA) is investigated using seven series of concretes: the first is the control series, containing all natural aggregates and no nano silica. In the second and third series, 25% and 50% (by weight) natural coarse aggregates are replaced by RCA, respectively. Effects of nano silica on concretes containing RCA are evaluated in the remaining series: in the fourth and fifth, 1% and 2% (by weight) nano silica is added to concrete containing 25% RCA, respectively. Similar nano silica additions are used in the sixth and seventh series, but the RCA content is 50%. Compressive and tensile strengths of all concretes are evaluated after 7, 28 and 56 d of water curing. Concrete durability properties, such as sorptivity, volume of permeable voids and chloride penetration, are also evaluated after 7 and 28 d of water curing. Addition of nano silica is found to significantly improve compressive strength of concrete containing 25% RCA at all ages; however, no such improvement is observed in concrete containing 50% RCA. An opposite scenario is observed for tensile strength, where nano silica addition showed improvement in concrete containing 50% RCA. The addition of nano silica also exhibited improvement in the durability properties of concretes containing 25% and 50% RCA.